Profiling the Secretome and Extracellular Proteome of the Potato Late Blight Pathogen Phytophthora infestans - Meijer, Harold J. G. (The American Society for Biochemistry and Molecular Biology, 2014)
Oomycetes are filamentous organisms that cause notorious diseases, several of which have a high economic impact. Well known is Phytophthora infestans, the causal agent of potato late blight. Previously, in silico analyses of the genome and transcriptome of P. infestans resulted in the annotation of a large number of genes encoding proteins with an N-terminal signal peptide. This set is collectively referred to as the secretome and comprises proteins involved in, for example, cell wall growth and modification, proteolytic processes, and the promotion of successful invasion of plant cells. So far, proteomic profiling in oomycetes was primarily focused on subcellular, intracellular or cell wall fractions; the extracellular proteome has not been studied systematically. Here we present the first comprehensive characterization of the in vivo secretome and extracellular proteome of P. infestans. We have used mass spectrometry to analyze P. infestans proteins present in seven different growth media with mycelial cultures and this resulted in the consistent identification of over two hundred proteins. Gene ontology classification pinpointed proteins involved in cell wall modifications, pathogenesis, defense responses, and proteolytic processes. Moreover, we found members of the RXLR and CRN effector families as well as several proteins lacking an obvious signal peptide. The latter were confirmed to be bona fide extracellular proteins and this suggests that, similar to other organisms, oomycetes exploit non-conventional secretion mechanisms to transfer certain proteins to the extracellular environment.